(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
This session presented EmpowerHer, a European initiative that explores how reflective and digital practices can support the recognition of competences acquired by migrant women in informal and non-formal contexts. EmpowerHer brings together partners from Germany, France, Cyprus, Portugal, and Spain to support migrant women’s integration into employment. Funded under the Erasmus+ program (KA220-ADU), it develops a comprehensive approach that values migrant women’s competences and life experiences and makes them more visible to employers and society. Research across Europe highlights the multiple barriers migrant women face in the labor market, often described as a "double disadvantage" shaped by the intersection of gender and migration-related challenges. In response, EmpowerHer adopts a holistic framework operating at three levels: at the individual level, supporting migrant women in identifying, documenting, and confidently articulating competences, drawing on the concept of self-efficacy; at the organizational level, addressing employers’ roles by promoting inclusive onboarding and diversity-sensitive workplace practices; and at the structural level, drawing on perspectives such as super-diversity to inform guidance and employer-facing strategies aimed at longer-term change in workplaces and beyond. Operationally, EmpowerHer integrates four interconnected elements. First, an adapted ProfilPASS portfolio tool supports guided self-reflection and competence documentation tailored to migrant women’s realities; it includes a reflection component on five future-oriented skills that structure the learning architecture across the training and the web app. Second, a modular training program addresses these five competence areas—digital competence, cooperation, communication, problem solving, and cultural sensitivity—linking reflection to concrete job-search and workplace situations. Third, a web-based application mirrors the same five areas through interactive, scenario-based exercises and supports flexible, self-directed practice through level-appropriate learning pathways. Fourth, an employer toolkit translates project insights into practical guidance for inclusive onboarding, mentoring, and communication, with attention to the realities of small and medium-sized enterprises. In a supplementary work phase, EmpowerHer is gathering additional perspectives and insights from participating migrant women through interviews and feedback sessions. These activities were intended to ensure that the voices and experiences of migrant women are reflected in the final project outputs and help to shape more inclusive labor market practices. This session shared the EmpowerHer’s approach, showing how the adapted ProfilPASS, the training program, and the online platform work together to support competence recognition and inclusive onboarding. It also outlined the employer toolkit and the participatory methods used to integrate migrant women’s voices, highlighting how these elements can support open recognition, self-directed learning, and pathways to employment. The project data sheds light on how informally and non-formally acquired skills can be made visible, how digital tools can enable inclusive learning, and how cultural sensitivity can be embedded in onboarding, pointing to benefits for migrant women, and for employers building diverse teams. Keywords: self-efficacy; migrant women; inclusive onboarding, competence recognition, informal and non-formal learning